Targeted STING Activation Using Modified Ultrasound‐Responsive Microbubbles Enhances Immune Checkpoint Blockade Against Melanoma - Sina Khorsandi; Kristin Huntoon; Yifan Wang; Adam Woodward; Abin Antony; Connor Endsley; Nazia Hafeez; Jared L. Edwards; Nicole McCuen; Prasanna G. Alluri; Betty Y.S. Kim; Wen Jiang; et al. (Advanced Science)
Abstract Despite the recent successes of immune checkpoint inhibitors (ICIs) in treating advanced melanoma, durable clinical responses still remain limited. To boost immune responses, agents that target immune regulators, such as the Stimulator of Interferon Genes (STING) agonist cyclic GMP‐AMP (cGAMP), are being investigated. However, their clinical translation is impeded by poor serum stability, rapid tissue clearance, and T‐cell death due to off‐target activation. Recently, a novel strategy termed Microbubble‐assisted UltraSound‐guided Immunotherapy of Cancer (MUSIC) has been reported to selectively deliver cGAMP directly into the cytosol of antigen‐presenting cells with spatiotemporal control. The resulting activation of STING and downstream proinflammatory pathways produces antitumor effects in murine models of breast cancer. Herein, this study reports that MUSIC provides curative results in aggressive murine models of melanoma as well. Under ultrasound exposure, MUSIC reduces tumor size, increases overall survival, and synergizes with ICIs to bridge innate and adaptive immunities. The results from this study represent MUSIC's ability to produce potent immune responses in melanoma, thus indicating its potential as an adjuvant for cancers where ICI is the current standard of care.